Synovial sarcoma of the hypopharynx in a pediatric patient: Case report. (2016) - Alotaibi, N.H.; Bornand, Aurélie; Dulguerov, Nicolas; Becker, M.; Dulguerov, Pavel
Highlights: Synovial sarcoma (SS) is an extremely rare head and neck malignancy in the pediatric population. Preoperative diagnosis of SS is challenging because of its nonspecific symptomatology, low clinical morbidity at presentation, lack of specific radiologic features, and physicians unfamiliarity. We present this case to emphasize the correlation between histopathology diagnosis and clinical judgment to perform optimal treatment (surgical, chemo and/or radiotherapy) with preservation of pharyngeo-laryngeal function in the pediatric population. Abstract: Introduction: Synovial sarcoma (SS) is uncommon high grade soft tissue sarcoma, accounting for less than 10% of all head and neck sarcomas. Also, about 10% of SS occur within the Head & Neck. In the pediatric population, SS is an extremely rare head & neck malignancy. Presentation of case: We present a case of sixteen years old boy diagnosed with SS situated of the hypopharynx treated by surgical excision and post operative radio-chemotherapy. Discussion: This anatomical location brings additional functional challenges (swallowing, phonation, respiration), especially in the pediatric population. Pre-operative and even post-operative histopathological diagnosis of SS remains difficult. Optimal treatment of Head & Neck SS has to balance functional and oncologic aspects. Conclusion: SS is an extremely rare head & neck malignancy in pediatric population. It has multifaceted challenges including pre and post-operative histopathological diagnosis and optimal modality of treatment. Clinical judgment, especially in the pediatric population, needs to balance tumor free margins and organ preservation in head and neck region.